Silicon photonics for telecommunications and biomedicine - Fathpour, Sasan; Jalali, B. (CRC Press, 2012)
"Focusing on the important obstacles to be met in order to make silicon photonics a viable commercial reality, this book provides a concise introduction to major developments in the field. Worldwide experts provide clear explanations of the fundamentals and state-of-the-art approaches. After a historical review, the text discusses the critical areas of silicon wire waveguides and optical parametric effects in silicon, stress and piezoelectric tuning of silicon's optical properties, and short pulse techniques in silicon photonics. It also addresses silicon-based optical resonators, mid-wavelength infrared applications, growth techniques, hybrid lasers on silicon, and energy harvesting."--